Adult-onset spinal teratoma: a case report and review - K. Blank; G. Terbetas; L. Neverauskienė; J. Ušinskienė (Neurologijos seminarai)
Teratoma is defined as a neoplasm that is composed of a variety of parenchymal cell types derived from three germinal layers (endoderm, mesoderm and ectoderm). Teratomas of the spinal cord constitute 0.1-0.5% of all spinal tumors, and these lesions are extremely rare in adults. Intramedular spinal teratoma is the most common type of spinal teratomas. The main spinal teratoma symptoms are pain, weakness and numbness of the legs, sphincter and/or gait dysfunction; intramedullary teratomas present early with increased reflexes and loss of vesical and rectal control. Histopathologic examination is the gold standard for definite diagnosis. Teratomas are diagnosed when remnants of all three germ layers are present. MRI is the gold standard diagnostic technique for spinal teratoma. The tumor presents as inhomogeneus intensities in both T1- and T2-weighted images due to teratoma’s tissue heterogeneity. Surgical resection is the first line treatment for spinal teratoma, usually decompressive laminectomy is performed. The goal of surgery should always be the most radical removal possible with relieve of the nerve compression with the aim of preventing progressive deterioration. The authors describe the first case of intradural intramedullary teratoma in Lithuania, which did not present with typical spinal teratoma symptoms and signs, its successful diagnosis and treatment; literature review of adult-onset spinal teratomas is also presented.